Changes in relative demand for labour in Malaysia (1984-1997) using a decompsition approach - Said, Rusmawati; Haris, Asmaddy (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
This paper is concerned with the two main causes of wage differentials in the Malaysian labour market during the period 1984-1997. These are the impact of changes in trade patterns and technological change. The paper has employed set of data comprises micro-level data from the Household Income Survey (HIS) for several years during the period 1984 to 1997. The main finding of this paper is that changes in the relative demand for labour favour middle level of education (secondary levels of education) workers and that technological change is the main explanation for the changing pattern of employment in the Malaysian economy. The paper finds that changes in the pattern of trade have had only small effects in explaining the changes in the relative demand for labour.